Kajian Epistemologis Iklan Politik dan Perilaku Memilih dalam Dinamika Pemilu 2009 - Setianto, Widodo Agus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2009)
This paper elaborates theoretical explanation of political ads phenomena, the image of the party and voting behavior. The use of political ads has been increasing in various political events such as legislative election, presidential elections and local election since the post new order era. Theoretical explanation suggests that political ads as a form of political communication has a role in the formation affect the image and the voter behavior.